Percutaneous Management of Bile Leaks - Marchak, Katherine; Singh, Davinder; Trivedi, Premal (Digestive Disease Interventions, 2025)
Biliary leaks can occur as complications of many surgical procedures and as a result of trauma. Although some leaks can be managed conservatively, a significant proportion requires invasive intervention, percutaneously, endoscopically, and/or surgically. This review provides a general approach to the evaluation and management of bile leaks and describes treatment options along with associated efficacy, with the goal of facilitating, in the absence of definitive guidelines, informed decision-making on a case-by-case basis.
Keywords: interventional radiology; postoperative complications; biliary leak